PERFORMANCE ANALYSIS OF SUPERVISORY CONSULTANTS IN ROAD CONSTRUCTION PROJECTS IN THE PROVINCE WEST SUMATRA - Perdana, Marzuky; Rita, Eva; Peli, Martalius (Rang Teknik Journal, 2025)
This research discusses the performance analysis of supervisory consultants in road construction projects in West Sumatra Province. The objectives to be achieved with this research are to identify factors that influence the performance of supervisory consultants on road construction projects in West Sumatra province, to analyze the dominant factors that influence the performance of supervisory consultants on road construction projects in West Sumatra province, and to obtain solutions. to improve the performance of supervisory consultants on road construction projects in West Sumatra province. In this research the author used a combined research method, namely by distributing questionnaires to respondents and conducting interviews with experts. The selected respondents were owners, namely the Department of Highways, Human Settlements and Spatial Planning of West Sumatra Province, consultants and contractors involved in Periodic Road Maintenance work activities in West Sumatra Province in the 2018 to 2023 Fiscal Year. The research results showed that there were 10 factors that influenced performance supervising consultants for a road construction project in West Sumatra Province and the dominant factors influencing it.